(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The term Social Exclusion possess a great popularity among intellectuals and policy makers not only in India but worldwide for it enables locating the gaps for the development of the marginalized sections and downtrodden for the concerned country.